Adenosine-Stress Dynamic Myocardial Perfusion Imaging With Second-Generation Dual-Source CT: Comparison With Conventional Catheter Coronary Angiography and SPECT Nuclear Myocardial Perfusion Imaging - Wang, Yining; Qin, Ling; Shi, Ximin; Zeng, Yong; Jing, Hongli; Schoepf, U. Joseph; Jin, Zhengyu (American journal of roentgenology (1976), 2012)
The purpose of this article is to evaluate the feasibility of adenosine-stress dynamic myocardial perfusion imaging (MPI) with 128-MDCT dual-source CT for detecting myocardial ischemia in comparison with conventional catheter coronary angiography and nuclear MPI. Thirty patients (21 men and nine women; mean [± SD] age, 59.2 ± 7.6 years) prospectively underwent a combined stress CT perfusion and CT angiography (CTA) examination. Complete time-attenuation curves of the myocardium were acquired with prospectively ECG-triggered axial images at two alternating positions. Myocardial blood flow (MBF) was quantified according to dynamic CT perfusion, and MBF values of normal and abnormal segments were compared. Findings on CT perfusion were compared with those for stress and rest SPECT. Perfusion defects according to CT were correlated to flow-obstructing stenosis detected on CTA and catheter coronary angiography. On stress CT perfusion, 19 patients (63%) and 83 of 504 segments (16%) had perfusion abnormalities. There was a significant difference in MBF values between normal (142.9 ± 30.6 mL/100 mL/min) and hypoperfused (90.0 ± 22.8 mL/100 mL/min) segments (p < 0.001). With nuclear MPI results as a comparison, the sensitivity, specificity, positive predictive value, and negative predictive value of CT perfusion for identifying segments with perfusion defects were 0.85, 0.92, 0.55, and 0.98, respectively. On a per-vessel basis, sensitivity, specificity, positive predictive value, and negative predictive value for detecting flow-obstructing stenosis were, respectively, 1.00, 0.757, 0.541, and 1.00 for CT perfusion; 0.90, 0.514, 0.346, and 0.947 for CTA; and 0.90, 0.814, 0.581, and 0.966 for CT perfusion combined with CTA. Adenosine-stress CT perfusion detects myocardial perfusion defects in good correlation with nuclear MPI. CT perfusion combined with CTA improves the diagnostic accuracy for identifying flow-obstructing stenosis compared with CTA alone.